Factors Influencing in Adoption of Livestock Insurance with Special Reference to Haryana - Singh, Shyam Prakash; Chandel, Balwant Singh (Indian Journal of Dairy Science, 2019)
In spite of the concerted efforts put forth by the Government, the adoption of livestock insurance is very low i.e. 0.68 per cent of the milch animals were insured in 2012-13 in the country. The reasons for its lack of adoption could be related with implementation and efficacy of the scheme, and socio-economic conditions of the farmer. In logit relationship, the paper found that increase in herd size and share of crossbred animals in the herd raised the probability to adopt the livestock insurance. The concerted efforts on the part of Government, Extension and Research Organizations to promote commercialization of dairy farming and up-gradation of germplasm of animals will go a long way in supporting the livestock insurance in the country.Â